ANALISA PROKSIMAT TEPUNG DARI BERBAGAI BAGIAN TUBUH CUMI (LOLIGO SP) - Wittriansyah, Khoeruddin; Kristiningsih, Ari (Science Technology and Management Journal, 2024)
Squid (Loligo sp) is a potential fishery commodity in Indonesia.Squid consumption in Indonesia is dominated by fresh squid product. There are not many diversified squid products. The flouring process is one form of diversification of squid product.Squid flour can be used as processed food such as cakes or as an additional flavoring to food. The quality of flour is determined by the proximate content of the flour. This research aims to determine the nutritional content through proximate analysis of squid flour. Squid flour is processed from the head, body, and ink of squid. The squids body parts are cleaned, weighed, and then dried in an oven. The next procedures is proximate analysis. The results showed that the highest protein content was found in squid body flour (68.98%), and the lowest was in squid ink flour (50.87%). The highest fat content was found in squid head flour (4.91%) and the lowest in squid ink flour (2.59%). The highest water content was found in squid ink flour, 15.32 (%) and the lowest in squid body flour (3.22%).